Elimination of undifferentiated human embryonic stem cells by cardiac glycosides - Yu-Tsen Lin (Nature Portfolio, 2017)
Abstract An important safety concern in the use of human pluripotent stem cells (hPSCs) is tumorigenic risk, because these cells can form teratomas after an in vivo injection at ectopic sites. Several thousands of undifferentiated hPSCs are sufficient to induce teratomas in a mouse model. Thus, it is critical to remove all residue-undifferentiated hPSCs that have teratoma potential before the clinical application of hPSC-derived cells. In this study, our data demonstrated the cytotoxic effects of cardiac glycosides, such as digoxin, lanatoside C, bufalin, and proscillaridin A, in human embryonic stem cells (hESCs). This phenomenon was not observed in human bone marrow mesenchymal stem cells (hBMMSCs). Most importantly, digoxin and lanatoside C did not affect the stem cells’ differentiation ability. Consistently, the viability of the hESC-derived MSCs, neurons, and endothelium cells was not affected by the digoxin and lanatoside C treatment. Furthermore, the in vivo experiments demonstrated that digoxin and lanatoside C prevented teratoma formation. To the best of our knowledge, this study is the first to describe the cytotoxicity and tumor prevention effects of cardiac glycosides in hESCs. Digoxin and lanatoside C are also the first FDA-approved drugs that demonstrated cytotoxicity in undifferentiated hESCs.